The Safe Administration of Remdesivir in a Patient with Acute Kidney Injury Requiring Hemodialysis. (29th December 2020) - Peyko, Vincent; Ladd, Helena; Cutrona, Anthony
Abstract : Remdesivir is a nucleoside analog prodrug with broad-spectrum antiviral activity, including against coronaviruses. This has prioritized the inclusion of remdesivir in coronavirus disease 2019 (COVID-19) clinical trials. The United States Food and Drug Administration has granted emergency use authorization for remdesivir. This emergency use authorization does not recommend the use of remdesivir in patients with estimated glomerular filtration rate (eGFR) less than 30 mL/min unless the benefits outweigh the risks. To date, there are no studies and scant information in the literature evaluating remdesivir utilization in patients with eGFR less than 30 mL/min or receiving hemodialysis. With little utilization data for patients with acute or chronic kidney injury, remdesivir may not be considered, leaving this patient population without the opportunity of a potentially beneficial treatment option. We present a case of one patient with eGFR less than 30 mL/min that required hemodialysis in which remdesivir was safely initiated, with therapy completed without any serious adverse events.